Electronic device, rotating shaft, layered composite material and manufacturing method thereof

By using high yield strength metal materials and diamond-containing composite materials in the shaft of electronic equipment, the problem of heat generated by friction of the rotating shaft in the prior art is solved, the resistance to drop, wear and thermal conductivity is improved, and the resistance to drop, wear and thermal conductivity is improved, and the User experience and device performance.

CN114103302BActive Publication Date: 2025-02-18HUAWEI TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202010864702.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-08-25
Publication Date
2025-02-18
Estimated Expiration
2040-08-25

AI Technical Summary

Technical Problem

The rotation shaft of existing electronic equipment generates heat due to friction during rotation, resulting in poor resistance to drop, wear resistance and thermal conductivity, affecting the overall heat dissipation effect and user experience.

Method used

A layered composite material is used, including at least two material layers, wherein the first material layer uses a metal material with high yield strength and high elongation, and the second material layer uses a composite material containing diamond particles, and is denseized by a metal injection molding process. Forming.

Benefits of technology

The fracture resistance, wear resistance and heat dissipation performance of the rotating shaft are improved, thereby improving the user experience and ensuring the normal operation of electronic equipment and signal transmission stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114103302B_ABST
    Figure CN114103302B_ABST
Patent Text Reader

Abstract

An embodiment of the present application provides an electronic device, a rotating shaft, a layered composite material and a method for manufacturing the same. The layered composite material includes at least two stacked material layers, wherein the at least two material layers include adjacent first material layers and second material layers, the first material layer uses a first metal material, the yield strength of the first metal material is greater than 200 MPa, and the elongation of the first metal material is greater than 6%; the second material layer uses a first composite material, and the first composite material includes a second metal material and diamond particles. In this way, while ensuring the anti-fracture performance and wear resistance of the rotating shaft, the thermal conductivity and heat dissipation performance of the rotating shaft are improved, thereby improving the user experience.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present application relate to the field of terminal technology, and in particular to an electronic device, a rotating shaft, a layered composite material, and a manufacturing method thereof. Background Art

[0002] Mobile phones, computers and other electronic devices have become inseparable from our lives. They can be seen everywhere in our lives and have greatly improved people's living standards. With the rapid development of communication equipment technology, the functions of electronic products such as laptops, folding screen mobile phones, and tablets have gradually increased, and energy consumption has also increased. Consumers have also put forward higher and higher requirements for the performance of electronic products. Among them, heat dissipation is a key factor related to the performance of electronic products. Therefore, the heat dissipation problem of electronic products has become more and more serious. Some manufacturers are considering adding heat conduction function to the shaft of electronic products to reduce the temperature of the host heating area of ​​electronic products, such as the chip area, to achieve balanced heat conduction, which is beneficial to the overall heat dissipation effect of electronic products.

[0003] Taking a laptop computer as an example, the rotation axis of the laptop computer includes a fixed part and a rotating part rotatably connected to the fixed part, and the rotating part is used to connect the display screen of the laptop computer and the computer base to realize the folding and unfolding of the laptop computer. In the prior art, the fixed part and the rotating part in the rotation axis are usually made of aluminum alloy or copper alloy.

[0004] However, since the rotating part will cause friction and generate heat when they contact each other when rotating around the fixed part, the above-mentioned shaft has poor drop resistance, wear resistance and thermal conductivity. The poor drop resistance and wear resistance cause the entire laptop to be easily worn, loosened or even broken during rotation. The poor thermal conductivity leads to poor overall heat dissipation of the laptop, which greatly affects the experience of the laptop. Summary of the invention

[0005] The present application provides an electronic device, a rotating shaft, a layered composite material and a manufacturing method thereof, which improves the thermal conductivity and heat dissipation performance of the rotating shaft while ensuring the anti-fracture performance and wear resistance of the rotating shaft, thereby improving the user experience.

[0006] In a first aspect, the present application provides a layered composite material, comprising: at least two material layers stacked together; wherein the at least two material layers include adjacent first material layers and second material layers; the first material layer uses a first metal material, the yield strength of the first metal material is greater than 200 MPa, and the elongation of the first metal material is greater than 6%; the second material layer uses a first composite material, and the first composite material includes a second metal material and diamond particles.

[0007] The layered composite material provided in the embodiment of the present application includes at least two material layers stacked together. The first material layer of the at least two material layers adopts a first metal material, the yield strength of the first metal material is greater than 200Mpa, and the elongation of the first metal material is greater than 6%, which can ensure the strength and fracture resistance of the layered composite material. The second material layer of the at least two material layers adopts a first composite material, and the first composite material includes a second metal material and diamond particles, which can ensure the wear resistance, thermal conductivity and heat dissipation performance of the layered composite material.

[0008] In a possible implementation, the diamond particles are at least partially located on the surface of the second material layer away from the first material layer. In this way, at least part of the second material layer is located on the side of the second material layer that is not in contact with the first material layer, which can ensure the wear resistance, thermal conductivity and heat dissipation performance of the surface of the layered composite material.

[0009] In a possible implementation, a third material layer is further included which is bonded to the second material layer, and the second material layer is disposed between the first material layer and the third material layer; the third material layer is made of diamond. Diamond has good wear resistance and thermal conductivity. Diamond is bonded to the second material layer and is located on the side of the second material layer away from the first material layer, which can ensure the wear resistance, thermal conductivity and heat dissipation performance of the surface of the layered composite material. Moreover, due to the padding of the first material layer and the second material layer, it is more conducive to the diamond of the third material layer to achieve extreme thermal conductivity and extreme hardness.

[0010] In a possible implementation, the third material layer is exposed on one side facing away from the second material layer. In this way, the third material layer is located at the outermost layer of the layered composite material, which is conducive to further achieving the ultimate thermal conductivity and extreme hardness of the layered composite material.

[0011] In a possible implementation, the first metal material and the second metal material have the same main element, and the main element is the element with the largest proportion in the first metal material and the second metal material. In this way, the element with the largest proportion in the first metal material is the same as the element with the largest proportion in the second metal material, which can ensure a tighter connection between the first metal material and the second metal material.

[0012] In a possible implementation, the first metal material includes one of a copper alloy and pure copper, and the second metal material includes one of a copper alloy and pure copper. Copper alloy and pure copper have good strength and elongation, which can ensure the strength and fracture resistance of the layered composite material. In a possible implementation, the first metal material includes one of stainless steel and alloy steel, and the second metal material includes one of stainless steel and alloy steel. Stainless steel and alloy steel have better yield strength and elongation, which can further improve the strength and fracture resistance of the layered composite material.

[0013] In a possible implementation, the first composite material further includes molybdenum sulfide particles. Molybdenum sulfide is a lubricating material with a self-lubricating effect, thereby ensuring that the layered composite material has a certain lubricating property while being wear-resistant. Moreover, molybdenum sulfide can also play a role in filling the concave area together with copper during the friction process.

[0014] In a possible implementation, the average particle size of the molybdenum sulfide particles is less than 15 um. The average particle size of the molybdenum sulfide particles is less than 15 um, so that the uniformity of the mixed material in the first composite material can be ensured.

[0015] In a possible implementation, the average particle size of the diamond particles is less than 10 um. The average particle size of the diamond particles is less than 10 um, so that the uniformity of the mixed material in the first composite material can be ensured.

[0016] In a possible implementation, the volume fraction of the diamond particles in the first composite material is greater than or equal to 5%. By making the volume fraction of the diamond particles greater than or equal to 5%, the proportion of the diamond particles in the second composite material can ensure the hardness, wear resistance and heat conduction effect of the second material layer.

[0017] In a possible implementation, the volume fraction of the diamond particles in the first composite material is greater than or equal to 25%. By increasing the volume fraction of the diamond particles, the proportion of the diamond particles in the second composite material is increased, thereby further improving the hardness, wear resistance and heat conduction effect of the second material layer.

[0018] In a possible implementation, the layered composite material is formed between the first material layer and the second material layer by a metal injection molding process. By forming the layered composite material by a metal injection molding process, the first material layer and the second material layer can be densified.

[0019] In a possible implementation, the thickness of the second material layer is greater than 0.1 mm. The thickness of the second material layer is greater than 0.1 mm, so that the hardness, wear resistance and heat conduction and heat transfer effect of the second material layer can be ensured.

[0020] In a possible implementation, the thickness of the third material layer is less than 10 um. The thickness of the third material layer is less than 10 um, which is conducive to achieving the ultimate thermal conductivity effect of the layered composite material.

[0021] The second aspect of the present application provides another layered composite material, comprising: at least two material layers stacked together; wherein the at least two material layers include adjacent first material layers and second material layers; the first material layer uses a first metal material, the yield strength of the first metal material is greater than 200 MPa, and the elongation of the first metal material is greater than 6%; the second material layer uses a first composite material, and the first composite material includes a second metal material and carbide particles.

[0022] The layered composite material provided in the embodiment of the present application includes at least two material layers stacked together. The first material layer among the at least two material layers adopts a first metal material, the yield strength of the first metal material is greater than 200Mpa, and the elongation of the first metal material is greater than 6%, which can ensure the strength and fracture resistance of the layered composite material. The second material layer among the at least two material layers adopts a first composite material, and the first composite material includes a second metal material and carbide particles, which can ensure the wear resistance of the layered composite material.

[0023] In a possible implementation, the carbide particles are at least partially located on the surface of the second material layer away from the first material layer. In this way, at least part of the second material layer is located on the side of the second material layer that is not in contact with the first material layer, which can ensure the wear resistance of the surface of the layered composite material.

[0024] In a possible implementation, a third material layer is further included which is bonded to the second material layer, and the second material layer is disposed between the first material layer and the third material layer; the third material layer is made of carbide. Diamond has good wear resistance, and the diamond is bonded to the second material layer and is located on the side of the second material layer away from the first material layer, which can ensure the wear resistance of the surface of the layered composite material. Moreover, due to the padding of the first material layer and the second material layer, it is beneficial for the carbide of the third material layer to achieve extreme hardness.

[0025] In a possible implementation, the third material layer is exposed on one side facing away from the second material layer. In this way, the third material layer is located at the outermost layer of the layered composite material, which is conducive to further achieving the ultimate hardness of the layered composite material.

[0026] In a possible implementation, the first metal material and the second metal material have the same main element, and the main element is the element with the largest proportion in the first metal material and the second metal material. In this way, the element with the largest proportion in the first metal material is the same as the element with the largest proportion in the second metal material, which can ensure a tighter connection between the first metal material and the second metal material.

[0027] In a possible implementation, the first metal material includes one of a copper alloy and pure copper, and the second metal material includes one of a copper alloy and pure copper. Copper alloy and pure copper have good strength and elongation, and can ensure the strength and fracture resistance of the layered composite material.

[0028] In a possible implementation, the first metal material includes one of stainless steel and alloy steel, and the second metal material includes one of stainless steel and alloy steel. Stainless steel and alloy steel have better yield strength and elongation, which can further improve the strength and fracture resistance of the layered composite material.

[0029] In a possible implementation, the first composite material further includes molybdenum sulfide particles. Molybdenum sulfide is a lubricating material with a self-lubricating effect, thereby ensuring that the layered composite material has a certain lubricating property while being wear-resistant. Moreover, molybdenum sulfide can also play a role in filling the concave area together with copper during the friction process.

[0030] In a possible implementation, the average particle size of the molybdenum sulfide particles is less than 15 um. The average particle size of the molybdenum sulfide particles is less than 15 um, so that the uniformity of the mixed material in the first composite material can be ensured.

[0031] In a possible implementation, the average particle size of the carbide particles is less than 10 um. The average particle size of the carbide particles is less than 10 um, so that the uniformity of the mixed material in the first composite material can be ensured.

[0032] In a possible implementation, the volume fraction of the carbide particles in the first composite material is greater than or equal to 5%. By making the volume fraction of the carbide particles greater than or equal to 5%, the proportion of diamond particles in the second composite material can ensure the hardness and wear resistance of the second material layer.

[0033] In a possible implementation, the volume fraction of the carbide particles in the first composite material is greater than or equal to 25%. By increasing the volume fraction of the carbide particles, the proportion of diamond particles in the second composite material is increased, thereby further improving the hardness and wear resistance of the second material layer.

[0034] In a possible implementation, the layered composite material is formed between the first material layer and the second material layer by a metal injection molding process. By forming the layered composite material by a metal injection molding process, the first material layer and the second material layer can be densified.

[0035] In a possible implementation, the thickness of the second material layer is greater than 0.1 mm. The thickness of the second material layer is greater than 0.1 mm, so that the hardness and wear resistance of the second material layer can be ensured.

[0036] A third aspect of an embodiment of the present application provides a rotating shaft, comprising a fixed part and a rotating part rotatably connected to the fixed part, wherein either the rotating part and the fixed part or both the rotating part and the fixed part are made of any of the above-mentioned layered composite materials.

[0037] The rotating shaft provided in the embodiment of the present application, by adopting the above-mentioned layered composite material, has improved thermal conductivity compared with the rotating shaft in the prior art, and can not only bear the force and rotate, but also have the effect of heat dissipation and heat conduction.

[0038] A fourth aspect of an embodiment of the present application provides an electronic device, comprising at least the rotating shaft described above.

[0039] The electronic device provided in the embodiment of the present application optimizes the experience of the electronic device by providing the above-mentioned rotating shaft, compared with the electronic device in the prior art, which has a very low thermal conductivity of the rotating shaft, and only plays the role of bearing force and rotating, but does not play the role of heat dissipation. At the same time, it can ensure the stability of signal transmission in the electronic device and ensure the normal operation of the electronic device.

[0040] A fifth aspect of an embodiment of the present application provides a method for manufacturing a layered composite material, comprising: providing at least a first metal material and a first composite material; wherein the first metal material is used as a first material layer, the yield strength of the first metal material is greater than 200 MPa, and the elongation of the first metal material is greater than 6%; the first composite material is used as a second material layer, and the first composite material includes a second metal material and diamond particles; the first material layer and the second material layer are connected to form the layered composite material.

[0041] The method for manufacturing a layered composite material provided in an embodiment of the present application forms a layered composite material by connecting a first material layer using a first metal material and a second material layer using a first composite material. The yield strength of the first metal material is greater than 200Mpa, and the elongation of the first metal material is greater than 6%, which can ensure the strength and fracture resistance of the layered composite material. Since the first composite material includes a second metal material and diamond particles, the wear resistance, thermal conductivity and heat dissipation performance of the layered composite material can be ensured.

[0042] In a possible implementation, the connecting the first material layer and the second material layer to form the layered composite material specifically includes: connecting the first material layer and the second material layer to form the layered composite material using a metal injection molding process. By using the metal injection molding process to form the layered composite material, the first material layer and the second material layer can be densified.

[0043] In a possible implementation, after the first material layer and the second material layer are connected to form a layered composite material, the method further includes: providing diamond, wherein the diamond serves as a third material layer; and arranging the third material layer between the second material layer and the first material layer in the layered composite material, wherein the third material layer is adjacent to the second material layer.

[0044] By providing a third material layer, the diamonds in the third material layer have good wear resistance and thermal conductivity, and the diamonds are attached to the second material layer and are located on the side of the second material layer away from the first material layer, which can ensure the wear resistance, thermal conductivity and heat dissipation performance of the surface of the layered composite material. Moreover, due to the padding of the first material layer and the second material layer, it is beneficial for the diamonds in the third material layer to achieve extreme thermal conductivity and extreme hardness. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 A schematic diagram of a structure of a layered composite material provided in an embodiment of the present application;

[0046] Figure 2 Another schematic diagram of the structure of the layered composite material provided in the embodiment of the present application;

[0047] Figure 3 A schematic structural diagram of a method for manufacturing a layered composite material provided in an embodiment of the present application;

[0048] Figure 4 Another structural schematic diagram of a method for manufacturing a layered composite material provided in an embodiment of the present application;

[0049] Figure 5 A schematic diagram of another structure of a method for manufacturing a layered composite material provided in an embodiment of the present application;

[0050] Figure 6 A schematic diagram of another structure of a method for manufacturing a layered composite material provided in an embodiment of the present application;

[0051] Figure 7 A schematic diagram of another structure of a method for manufacturing a layered composite material provided in an embodiment of the present application;

[0052] Figure 8A schematic diagram of the structure of the rotating shaft provided in an embodiment of the present application;

[0053] Fig. 9 A schematic diagram of the structure of an electronic device provided in an embodiment of the present application;

[0054] Fig.10 Another schematic diagram of the structure of an electronic device provided in an embodiment of the present application.

[0055] Description of reference numerals:

[0056] 100-electronic device; 1-rotating shaft; 101-fixed part; 102-rotating part; 2-first structural part; 3-second structural part; 10-first material layer; 20-second material layer; 30-third material layer. DETAILED DESCRIPTION

[0057] The terms used in the implementation method part of this application are only used to explain the specific embodiments of this application, and are not intended to limit this application. The implementation method of the embodiments of this application will be described in detail below with reference to the accompanying drawings.

[0058] like Figure 1 As shown, the present application embodiment provides a layered composite material, which may include: at least two material layers (i.e. Figure 1 The first material layer 10 and the second material layer 20 are arranged adjacent to the first material layer 10), wherein the first material layer 10 of at least two material layers can be made of a first metal material, the yield strength of the first metal material can be greater than 200 MPa, and the elongation of the first metal material can be greater than 6%. In this way, the high yield strength and high elongation of the first metal material can ensure the anti-drop and anti-fracture performance of the layered composite material.

[0059] Among them, the second material layer 20 of at least two material layers can adopt the first composite material, and the first composite material includes the second metal material and diamond particles, so that the wear resistance, thermal conductivity and heat dissipation performance of the layered composite material can be improved. The thermal conductivity of the first composite material can be greater than 300W / mk. For example, the thermal conductivity of the first composite material can be 350W / mk, 400W / mk, 450W / mk, etc.

[0060] In the embodiment of the present application, the diamond particles in the first composite material are at least partially located on the surface of the second material layer 20 away from the first material layer 10. In this way, at least part of the second material layer 20 is located on the side of the second material layer 20 that is not in contact with the first material layer 10, which can ensure the wear resistance, thermal conductivity and heat dissipation performance of the surface of the layered composite material.

[0061] In a possible implementation, the Vickers hardness of the first metal material may be greater than 100 HV, and the high Vickers hardness of the first metal material can ensure the wear resistance of the layered composite material.

[0062] In order to further improve the drop resistance, fracture resistance and wear resistance of the first metal material, the yield strength of the first metal material can be greater than 800 MPa, the elongation of the first metal material can be greater than 9%, and the Vickers hardness of the first metal material can be greater than 305 HV. Similarly, in order to further improve the thermal conductivity and heat dissipation performance of the first composite material, the thermal conductivity of the first composite material can be greater than 450 W / mk.

[0063] In one possible implementation, the thickness d1 of the second material layer 20 may be greater than 0.1 mm. For example, the thickness d1 of the second material layer 20 may be 0.1 mm, 0.15 mm, 0.2 mm, etc. The embodiment of the present application does not limit the thickness of the second material layer 20 and is not limited to the above examples.

[0064] In an embodiment of the present application, the first metal material may include one of a copper alloy or pure copper, that is, the first material layer 10 may use copper with high strength, high elongation and high thermal conductivity. The strength and elongation of the copper alloy and pure copper are good, which can ensure the strength and fracture resistance of the layered composite material. Among them, the average particle size of the copper alloy or pure copper can be less than 30um, and the copper mass fraction of the copper alloy or pure copper can be greater than 50%. In this way, the strength, mechanical reliability, elongation (anti-breakage) and good thermal conductivity of the first material layer 10 can be guaranteed. Similarly, the second metal material may also include one of a copper alloy or pure copper.

[0065] Of course, in some other embodiments, the first metal material may include one of stainless steel and alloy steel, and the second metal material may also include one of stainless steel and alloy steel, which is not limited in the present application and is not limited to the above examples. Stainless steel and alloy steel have better yield strength and elongation, which can further improve the strength and fracture resistance of the layered composite material.

[0066] In the embodiment of the present application, the main element of the first metal material is the same as that of the second metal material, and the main element is the element that accounts for the largest proportion in the first metal material and the second metal material. In other words, the element that accounts for the largest proportion in the first metal material is the same as the element that accounts for the largest proportion in the second metal material, which can ensure that the connection between the first metal material and the second metal material is tighter. For example, the first metal material and the second metal material can both contain copper alloys, the first metal material and the second metal material can both contain pure copper, or one of the first metal material and the second metal material can contain copper alloys, and the other of the first metal material and the second metal material can contain pure copper.

[0067] In some other embodiments, the first metal material and the second metal material may both contain stainless steel, the first metal material and the second metal material may both contain alloy steel, or one of the first metal material and the second metal material may contain stainless steel and the other of the first metal material and the second metal material may contain alloy steel.

[0068] In addition, it should be noted that the composition of the first composite material includes but is not limited to the following two possible implementation methods:

[0069] A possible implementation manner is: the first composite material is a layered composite material composed of a first metal material and diamond particles.

[0070] Another possible implementation manner is: the first composite material is a layered composite material composed of a first metal material, diamond particles, and molybdenum sulfide particles.

[0071] Among them, molybdenum sulfide is a lubricating material, and molybdenum sulfide particles have a self-lubricating effect, which can ensure that the layered composite material has a certain lubricating property while being wear-resistant. In addition, molybdenum sulfide can also play a role in filling the concave area together with copper during the friction process.

[0072] It should be noted that when the first metal material is a copper alloy, the first composite material is a layered composite material composed of copper alloy, diamond particles, and molybdenum sulfide particles, compared to the layered composite material in which the first composite material is pure copper, diamond particles, and molybdenum sulfide particles, it can ensure that the composition of the copper alloy in the first material layer 10 and the second material layer 20 is the same, thereby avoiding the situation where the two different materials cause a slight difference in shrinkage rate between the first material layer 10 and the second material layer 20 of the layered composite material.

[0073] Similarly, when the first metal material is pure copper, the first composite material is a layered composite material composed of pure copper, diamond particles, and molybdenum sulfide particles, compared to the first composite material being a layered composite material composed of copper alloy, diamond particles, and molybdenum sulfide particles, it can ensure that the pure copper composition in the first material layer 10 and the second material layer 20 is the same, thereby avoiding the situation where the two different materials cause a slight difference in shrinkage rate between the first material layer 10 and the second material layer 20 of the layered composite material.

[0074] As an optional embodiment, the average particle size of pure copper or copper alloy may be less than 30um. For example, the average particle size of pure copper or copper alloy may be 25um, 20um, 15um, etc. The embodiment of the present application does not limit the average particle size of pure copper or copper alloy, nor is it limited to the above examples.

[0075] The average particle size of the diamond particles may be less than 10 um. For example, the average particle size of the diamond particles may be 9 um, 8 um, 7 um, etc. The embodiment of the present application does not limit the average particle size of the diamond particles, nor is it limited to the above examples.

[0076] The average particle size of the molybdenum sulfide particles may be less than 15um. For example, the average particle size of the molybdenum sulfide particles may be 10um, 5um, 1um, etc. The embodiment of the present application does not limit the average particle size of the molybdenum sulfide particles, nor is it limited to the above examples.

[0077] It should be noted that the doping volume ratio of diamond particles to molybdenum sulfide particles is between 10-30%, wherein the volume doping ratio of diamond can be less than 25%, and the volume doping ratio of molybdenum sulfide can be less than 20%.

[0078] As an optional embodiment, the volume fraction of diamond particles in the first composite material may be greater than or equal to 5%. Further, the volume fraction of diamond particles in the first composite material may be greater than or equal to 25%. In the embodiment of the present application, by increasing the volume fraction of diamond particles, the hardness, wear resistance and heat conduction and heat transfer effect of the second material layer 20 can be further improved.

[0079] In the embodiment of the present application, the molding method between the first material layer 10 and the second material layer 20 includes but is not limited to the following two possible implementation methods:

[0080] One possible implementation is that a layered composite material can be formed between the first material layer 10 and the second material layer 20 by a metal injection molding process or a metal press molding process.

[0081] It should be noted that Metal Injection Molding (MIM) is a new powder metallurgy near-net molding technology derived from the plastic injection molding industry. Plastic injection molding technology produces various complex-shaped products at a low price, but the strength of plastic products is not high. In order to improve its performance, metal or ceramic powders can be added to the plastic to obtain products with higher strength and good wear resistance. In recent years, this idea has evolved into maximizing the content of solid particles and completely removing the binder and densifying the molded blank during the subsequent sintering process. This new powder metallurgy molding method is called metal injection molding.

[0082] The first material layer 10 and the second material layer 20 may contain a binder, for example, the binder may be an oil-based binder, the oil-based binder may be composed of paraffin and polypropylene, or the oil-based binder may be composed of paraffin, polypropylene and stearic acid. By providing a binder, the adjacent two layers of material (i.e., the first material layer 10 and the second material layer 20) can have a material component with the same properties, thereby enhancing the molding bonding between the first material layer 10 and the second material layer 20.

[0083] Another possible implementation is that a layered composite material can be formed between the first material layer 10 and the second material layer 20 by a powder pressing process. Powder pressing is a method of powder molding using external pressure in a die, also known as powder molding, and the pressing process consists of powder filling, pressing and demolding.

[0084] Another possible implementation is that a layered composite material can be formed between the first material layer 10 and the second material layer 20 by an insert die-casting process.

[0085] In the embodiments of this application, refer to the attached Figure 2 As shown, the at least two material layers may further include: a third material layer 30 , wherein the third material layer 30 is bonded to the second material layer 20 , and the second material layer 20 may be layered between the first material layer 10 and the third material layer 20 .

[0086] For example, the third material layer 30 can be arranged on the side of the second material layer 20 away from the first material layer 10, one side of the third material layer 30 is arranged in contact with one side of the second material layer 20, and the side of the third material layer 30 away from the second material layer 20 is exposed, that is, no material is arranged on the side of the third material layer 30 away from the second material layer 20. In this way, the third material layer 30 is located at the outermost layer of the layered composite material, so that the wear resistance and heat dissipation performance of the layered composite material can be further guaranteed.

[0087] In a possible implementation, the third material layer 30 may be formed on a surface of the second material layer 20 away from the first material layer 10 by a chemical vapor deposition process.

[0088] It should be noted that chemical vapor deposition is a chemical technology that mainly uses one or more gas phase compounds or single substances containing thin film elements to react chemically on the surface of a substrate to form a thin film. Chemical vapor deposition is a new technology for preparing inorganic materials developed in recent decades. It has been widely used in purifying substances, developing new crystals, and depositing various single crystal, polycrystalline or glassy inorganic thin film materials. These materials can be oxides, sulfides, nitrides, carbides, or binary or multi-element compounds in groups III-V, II-IV, and IV-VI, and their physical functions can be precisely controlled through the deposition process of gas phase doping.

[0089] As an optional embodiment, the Vickers hardness of the third material can be greater than the Vickers hardness of the first metal material, and the thermal conductivity of the third material layer 30 can be greater than the thermal conductivity of the first composite material. In this way, due to the padding of the first material layer 10 and the second material layer 20, it is beneficial for the third material layer 30 to achieve extreme thermal conductivity and extreme hardness. In the embodiment of the present application, the Vickers hardness of the third material layer 30 can be greater than 4000HV. For example, the Vickers hardness of the third material layer 30 can be 4500HV, 5000HV, 5500HV, etc. Of course, in order to further improve the hardness of the third material layer 30, the Vickers hardness of the third material layer 30 can be greater than 8000HV.

[0090] The thermal conductivity of the third material layer 30 may be greater than 1000 W / mk. For example, the thermal conductivity of the third material layer 30 may be 1500 W / mk, 2000 W / mk, 2500 W / mk, or the like.

[0091] In a possible implementation, the third material layer 30 may be made of diamond.

[0092] In the embodiment of the present application, the thickness d2 of the third material layer 30 may be less than 10um. For example, the thickness d2 of the third material layer 30 may be 9.5um, 9um, 8.5um, etc. The embodiment of the present application does not limit the thickness of the third material layer 30 and is not limited to the above examples.

[0093] In some other embodiments, the diamond particles can also be replaced with carbide particles, so that all functions other than the thermal conductivity of the layered composite material in the embodiment of the present application can still be achieved, for example, the carbide particles can still improve the wear resistance of the layered composite material. Of course, the copper alloy or pure copper in the first material layer 10 can also be replaced with other metal materials, such as stainless steel, alloy steel and other materials, which can further improve the yield strength of the first material layer 10 and increase the drop resistance, but the thermal conductivity of the overall first material layer 10 will be greatly reduced. Therefore, replacing the copper alloy or pure copper with stainless steel, alloy steel and other materials is at the expense of thermal conductivity, which is suitable for the situation where only the surface thermal conductivity of the layered composite material is required and the first material layer 10 does not need to dissipate heat.

[0094] It should be noted that in the embodiments of the present application, the layered composite material may include two material layers (a first material layer 10 and a second material layer 20), three material layers (a first material layer 10, a second material layer 20 and a third material layer 30), or more than three material layers, which are not limited in the embodiments of the present application. For example, other materials may be arranged below the first material layer 10 (i.e., the side of the first material layer 10 facing away from the second material layer 20) to adapt to different properties, so that the layered composite material has more properties and advantages.

[0095] like Figure 3 As shown, the embodiment of the present application also provides a method for manufacturing a layered composite material, which may include:

[0096] S101: Provide at least a first metal material and a first composite material, wherein the first metal material is used as a first material layer 10, the yield strength of the first metal material is greater than 200 MPa, and the elongation of the first metal material is greater than 6%, and the first composite material is used as a second material layer 20, and the first composite material may include a second metal material and diamond particles.

[0097] S102: Connect the first material layer 10 and the second material layer 20 to form a layered composite material.

[0098] As an optional implementation, refer to Figure 4 As shown, after S102, the method for manufacturing the layered composite material provided in the embodiment of the present application may further include:

[0099] S103 : providing diamond, where diamond serves as the third material layer 30 .

[0100] S104 : a third material layer 30 is disposed between the second material layer 20 and the first material layer 10 in the layered composite material, wherein the third material layer 30 is adjacent to the second material layer 20 .

[0101] Specifically, the third material layer 30 may be formed on a side of the second material layer 20 away from the first material layer 10 by a chemical vapor deposition process. For example, the second material layer 20 may be coated on a side away from the first material layer 10 to form a diamond film layer.

[0102] It should be noted that connecting the first material layer 10 and the second material layer 20 to form a layered composite material may specifically include:

[0103] S1021a: Using a metal injection molding process to connect the first material layer 10 and the second material layer 20 to form a layered composite material (refer to Figure 5 shown).

[0104] Specifically, when using the metal injection molding process, the first metal material and the binder can be mixed to form a first feed, and the first composite material and the binder can be mixed to form a first feed. Then, the first feed is selectively injected into the first material layer 10 of the layered composite material, and the second feed is selectively injected into the second material layer 20 of the layered composite material. Since the main components of the first feed and the second feed (i.e., the binder) are the same, they can be connected together. Then, the injected layered composite material is degreased, sintered and heat treated in sequence to form a layered composite material in which the first metal material is the first material layer 10 and the first composite material is the second material layer 20.

[0105] As an optional embodiment, the binder may be an oil-based binder, which may be composed of paraffin wax and polypropylene, or the oil-based binder may be composed of paraffin wax, polypropylene and stearic acid. By providing the binder, the adjacent two layers of material (i.e., the first material layer 10 and the second material layer 20) may have material components with the same properties, thereby enhancing the molding bonding between the first material layer 10 and the second material layer 20.

[0106] Alternatively, connecting the first material layer 10 and the second material layer 20 to form a layered composite material may specifically include:

[0107] S1021b: Using a powder pressing process to connect the first material layer 10 and the second material layer 20 to form a layered composite material (refer to Figure 6 shown).

[0108] Alternatively, connecting the first material layer 10 and the second material layer 20 to form a layered composite material may specifically include:

[0109] S1021c: Using an insert die-casting process to connect the first material layer 10 and the second material layer 20 to form a layered composite material (refer to Figure 7 shown).

[0110] Based on the above description, this application describes the structure, material composition and manufacturing method of the layered composite material in combination with specific scenarios, as follows:

[0111] Scene 1

[0112] In this scenario, the layered composite material can be a two-layer structure, wherein the first metal material used in the first material layer 10 can be a copper alloy, and the average particle size of the copper alloy is less than 20um, wherein the weight percentage of Mn in the first metal material is 28%, the weight percentage of Ni is 11.7%, the weight percentage of aluminum is 5%, the weight percentage of Si is 1.16%, and the rest is copper and impurities with a weight percentage of a single element less than 0.02%.

[0113] The first composite material used in the second material layer 20 can be a layered composite material composed of pure copper, diamond particles and molybdenum sulfide particles, wherein the average particle size of the diamond particles is less than 5um, and the average particle size of the molybdenum sulfide particles is less than 10um. After the pure copper, diamond particles and molybdenum sulfide particles are uniformly mixed, the volume proportion of the diamond particles is less than 5%, and the volume proportion of the molybdenum sulfide particles is less than 10%.

[0114] In this scenario, the metal injection molding process is used to connect the first material layer 10 and the second material layer 20 to form a layered composite material. First, the first metal material is combined with a binder to form a first feed, and the first composite material is combined with a binder to form a second feed (wherein the binder components of the first feed and the second feed are the same), and then the first feed is selectively injected into the first material layer 10 of the layered composite material, and the second feed is selectively injected into the second material layer 20 of the layered composite material. Since the main components of the first feed and the second feed (i.e., the binder) are the same, they can be connected together. It should be noted that when injecting the layered composite material, a single-material injection molding machine can be used to change the material and inject twice, or a double-material injection molding machine can be used for one injection.

[0115] Furthermore, the injected layered composite material is degreased, sintered and heat-treated in sequence to form a layered composite material in which the first metal material is the first material layer 10 and the first composite material is the second material layer 20. The processes of degreasing, sintering and heat treatment are described below:

[0116] Degreasing: first use CH2Cl2 for solvent degreasing, put the injected layered composite material into a water bath thermostat and immerse it, the degreasing temperature is 40 degrees Celsius, and the degreasing time is 3.5 hours; then dry the above degreased samples; then put the degreased samples into a tubular furnace for heating, and introduce hydrogen. The thermal degreasing time is to increase the temperature to 200 degrees Celsius at 2 degrees / min and keep it for 1 hour, then increase the temperature to 400 degrees Celsius at 1.5 degrees / min and keep it for 1 hour, then increase the temperature to 430 degrees at 2 degrees / min and keep it for 1 hour, then increase the temperature to 620 degrees at 2 degrees / min and keep it for 30 minutes, then increase the temperature to 880 degrees Celsius at 3 degrees / min and keep it for 1 hour before taking it out.

[0117] Sintering: The sintering furnace was pre-evacuated to 0.1 Pa, and then hydrogen was introduced at a gas flow rate of 0.12 cubic meters per hour; the sintering temperature was 1050 degrees Celsius and kept warm for 2 hours.

[0118] Heat treatment: The sintered parts are heat treated, with the solution temperature at 980 degrees Celsius for 2 hours and the aging temperature at 500 degrees Celsius for 2 hours.

[0119] In this scenario, a two-layer structure of a first material layer 10 (high-strength copper alloy) and a second material layer 20 (pure copper, diamond particles, molybdenum sulfide particles) is formed, wherein the first material layer 10 ensures the strength and elongation of the layered composite material, with a yield strength of 830 MPa, an elongation of 10%, and a Vickers hardness of 310 HV, ensuring that the material will not break when falling while greatly improving the wear resistance, and the second material layer 20 ensures thermal conductivity, wherein the thermal conductivity coefficient is >450 W / mk.

[0120] Compared with the existing technology that cannot have high strength, high thermal conductivity and high wear resistance, the layered composite material in this scenario can effectively concentrate the above functions on the same component.

[0121] Scene 2

[0122] In this scenario, the layered composite material can be a three-layer structure, wherein the first metal material used in the first material layer 10 can be a copper alloy, and the average particle size of the copper alloy is less than 25um, wherein the weight percentage of Mn in the first metal material is 25%, the weight percentage of Ni is 13%, the weight percentage of aluminum is 4%, the weight percentage of Si is 1.23%, and the rest is copper and impurities with a weight percentage of a single element less than 0.02%.

[0123] The first composite material used in the second material layer 20 can be a layered composite material composed of pure copper, diamond particles and molybdenum sulfide particles, wherein the average particle size of the diamond particles is less than 5um, and the average particle size of the molybdenum sulfide particles is less than 5um. After the pure copper, diamond particles and molybdenum sulfide particles are evenly mixed, the volume of the diamond particles accounts for 10%, and the volume of the molybdenum sulfide particles accounts for 10%.

[0124] In this scenario, the metal injection molding process is used to connect the first material layer 10 and the second material layer 20 to form a layered composite material. First, the first metal material is combined with a binder to form a first feed, and the first composite material is combined with a binder to form a second feed (wherein the binder components of the first feed and the second feed are the same), and then the first feed is selectively injected into the first material layer 10 of the layered composite material, and the second feed is selectively injected into the second material layer 20 of the layered composite material. Since the main components of the first feed and the second feed (i.e., the binder) are the same, they can be connected together. It should be noted that when injecting the layered composite material, a single-material injection molding machine can be used to change the material and inject twice, or a double-material injection molding machine can be used for one injection.

[0125] Furthermore, the injected layered composite material is degreased, sintered and heat-treated in sequence to form a layered composite material in which the first metal material is the first material layer 10 and the first composite material is the second material layer 20. The processes of degreasing, sintering and heat treatment are described below:

[0126] Degreasing: first use CH2Cl2 for solvent degreasing, put the injected layered composite material into a water bath thermostat and immerse it, the degreasing temperature is 50 degrees Celsius, and the degreasing time is 3 hours; then dry the above degreased samples; then put the degreased samples into a tubular furnace for heating, and introduce hydrogen. The thermal degreasing time is increased to 200 degrees Celsius at 1.5 degrees / min and kept warm for 1 hour, then increased to 400 degrees Celsius at 2 degrees / min and kept warm for 1 hour, then increased to 430 degrees at 2 degrees / min and kept warm for 1 hour, then increased to 620 degrees at 1.5 degrees / min and kept warm for 30 minutes, then increased to 880 degrees Celsius at 2 degrees / min and kept warm for 1 hour before taking out.

[0127] Sintering: The sintering furnace was pre-evacuated to 0.2 Pa, and then hydrogen was introduced at a gas flow rate of 0.12 cubic meters per hour; the sintering temperature was 1030 degrees Celsius and kept warm for 2 hours.

[0128] Heat treatment: The sintered parts are heat treated, with the solution temperature at 950 degrees Celsius for 3 hours and the aging temperature at 550 degrees Celsius for 2 hours.

[0129] After degreasing, sintering and heat treatment are sequentially performed on the injected layered composite material, a third material layer 30 is arranged on the side of the second material layer 20 in the layered composite material away from the first material layer 10. The third material used in the third material layer 300 may be diamond. Specifically, the third material layer 30 may be formed on the side of the second material layer 20 away from the first material layer 10 by chemical vapor deposition, that is, the side of the second material layer 20 away from the first material layer 10 may be coated to form a diamond film layer. For example, the layered composite material after heat treatment may be placed in a chemical vapor deposition (CVD) furnace for CVD coating to form a 5-micron thick diamond film layer.

[0130] In this scenario, a three-layer structure is formed by forming a first material layer 10 (high-strength copper alloy), a second material layer 20 (pure copper, diamond particles, molybdenum sulfide particles) and a third material layer 30 (diamond). The first material layer 10 ensures the strength and elongation of the layered composite material, with a yield strength of 800 MPa, an elongation of 9%, and a Vickers hardness of 305 HV, which ensures that the material will not break when it falls and greatly improves the wear resistance. The second material layer 20 ensures thermal conductivity, with a thermal conductivity coefficient of >450 W / mk. The third material layer 30 is a diamond film with a thermal conductivity coefficient of >1000 W / mk and a Vickers hardness of >8000 HV.

[0131] Compared with the above scenario one, the layered composite material in this scenario is made of three layers of materials, and the third material layer 30 can form extreme thermal conductivity and extreme hardness on the basis of the first material layer 10 and the second material layer 20 .

[0132] Scene 3

[0133] In this scenario, the layered composite material can be a three-layer structure, wherein the first metal material used in the first material layer 10 can be a copper alloy, and the average particle size of the copper alloy is less than 25um, wherein the weight percentage of Mn in the first metal material is 26%, the weight percentage of Ni is 10%, the weight percentage of aluminum is 5%, the weight percentage of Si is 1.12%, and the rest is copper and impurities with a weight percentage of a single element less than 0.02%.

[0134] The first composite material used in the second material layer 20 can be a layered composite material composed of pure copper, diamond particles and molybdenum sulfide particles, wherein the average particle size of the diamond particles is less than 3um, and after the pure copper, diamond particles and molybdenum sulfide particles are uniformly mixed, the volume proportion of the diamond particles is 25%.

[0135] In this scenario, the metal injection molding process is used to connect the first material layer 10 and the second material layer 20 to form a layered composite material. First, the first metal material is combined with a binder to form a first feed, and the first composite material is combined with a binder to form a second feed (wherein the binder components of the first feed and the second feed are the same), and then the first feed is selectively injected into the first material layer 10 of the layered composite material, and the second feed is selectively injected into the second material layer 20 of the layered composite material. Since the main components of the first feed and the second feed (i.e., the binder) are the same, they can be connected together. It should be noted that when injecting the layered composite material, a single-material injection molding machine can be used to change the material and inject twice, or a double-material injection molding machine can be used for one injection.

[0136] Furthermore, the injected layered composite material is degreased, sintered and heat-treated in sequence to form a layered composite material in which the first metal material is the first material layer 10 and the first composite material is the second material layer 20. The processes of degreasing, sintering and heat treatment are described below:

[0137] Degreasing: first use CH2Cl2 for solvent degreasing, put the injected layered composite material into a water bath thermostat and immerse it, the degreasing temperature is 50 degrees Celsius, and the degreasing time is 3 hours; then dry the above degreased samples; then put the degreased samples into a tubular furnace for heating, and introduce hydrogen. The thermal degreasing time is increased to 200 degrees Celsius at 1.5 degrees / min and kept warm for 1 hour, then increased to 400 degrees Celsius at 2 degrees / min and kept warm for 1 hour, then increased to 430 degrees at 1.5 degrees / min and kept warm for 1 hour, then increased to 620 degrees at 1.5 degrees / min and kept warm for 30 minutes, then increased to 880 degrees Celsius at 2 degrees / min and kept warm for 1 hour before taking out.

[0138] Sintering: The sintering furnace was pre-evacuated to 0.2 Pa, and then hydrogen was introduced at a gas flow rate of 0.12 cubic meters per hour; the sintering temperature was 1030 degrees Celsius and kept warm for 2 hours.

[0139] Heat treatment: The sintered parts are heat treated, with the solution temperature at 950 degrees Celsius for 3 hours and the aging temperature at 550 degrees Celsius for 2 hours.

[0140] After degreasing, sintering and heat treatment are sequentially performed on the injected layered composite material, a third material layer 30 is arranged on the side of the second material layer 20 in the layered composite material away from the first material layer 10. The third material used in the third material layer 300 may be diamond. Specifically, the third material layer 30 may be formed on the side of the second material layer 20 away from the first material layer 10 by chemical vapor deposition, that is, the side of the second material layer 20 away from the first material layer 10 may be coated to form a diamond film layer. For example, the heat-treated layered composite material may be placed in a chemical vapor deposition (CVD) furnace for CVD coating to form a 6-micron thick diamond film layer.

[0141] In this scenario, a three-layer structure is formed by forming a first material layer 10 (high-strength copper alloy), a second material layer 20 (pure copper, diamond particles, molybdenum sulfide particles) and a third material layer 30 (diamond). The first material layer 10 ensures the strength and elongation of the layered composite material, with a yield strength of 800 MPa, an elongation of 9%, and a Vickers hardness of 305 HV, which ensures that the material will not break when it falls and greatly improves the wear resistance. The second material layer 20 ensures thermal conductivity, with a thermal conductivity coefficient of >450 W / mk. The third material layer 30 is a diamond film with a thermal conductivity coefficient of >1000 W / mk and a Vickers hardness of >8000 HV.

[0142] Compared with the above scenario 2, the layered composite material in this scenario has more diamond particles, which can form better thermal conductivity, hardness and wear resistance. In other words, this scenario reduces the diamond particle size, increases the volume fraction of diamond particles, and uses more diamond particles as CVD film, thus forming a better quality diamond film.

[0143] Scene 4

[0144] In this scenario, the layered composite material can be a two-layer structure, wherein the first metal material used in the first material layer 10 can be a copper alloy, and the average particle size of the copper alloy is less than 20um, wherein the weight percentage content of Mn in the first metal material is 20%, the weight percentage content of Ni is 13%, the weight percentage content of aluminum is 6%, the weight percentage content of Si is 2%, and the rest is copper and impurities with a weight percentage of a single element less than 0.02%.

[0145] The first composite material used in the second material layer 20 can be a layered composite material composed of copper alloy, diamond particles and molybdenum sulfide particles, wherein the average particle size of the diamond particles is less than 5um, and the average particle size of the molybdenum sulfide particles is less than 10um. After the copper alloy, diamond particles and molybdenum sulfide particles are uniformly mixed, the volume proportion of the diamond particles is less than 10%, and the volume proportion of the molybdenum sulfide particles is less than 5%.

[0146] In this scenario, the metal injection molding process is used to connect the first material layer 10 and the second material layer 20 to form a layered composite material. First, the first metal material is combined with a binder to form a first feed, and the first composite material is combined with a binder to form a second feed (wherein the binder components of the first feed and the second feed are the same), and then the first feed is selectively injected into the first material layer 10 of the layered composite material, and the second feed is selectively injected into the second material layer 20 of the layered composite material. Since the main components of the first feed and the second feed (i.e., the binder) are the same, they can be connected together. It should be noted that when injecting the layered composite material, a single-material injection molding machine can be used to change the material and inject twice, or a double-material injection molding machine can be used for one injection.

[0147] Furthermore, the injected layered composite material is degreased, sintered and heat-treated in sequence to form a layered composite material in which the first metal material is the first material layer 10 and the first composite material is the second material layer 20. The processes of degreasing, sintering and heat treatment are described below:

[0148] Degreasing: first use CH2Cl2 for solvent degreasing, put the injected layered composite material into a water bath thermostat and immerse it, the degreasing temperature is 40 degrees Celsius, and the degreasing time is 3.5 hours; then dry the above degreased samples; then put the degreased samples into a tubular furnace for heating, and introduce hydrogen. The thermal degreasing time is to increase the temperature to 200 degrees Celsius at 2 degrees / min and keep it for 1 hour, then increase the temperature to 400 degrees Celsius at 1.5 degrees / min and keep it for 1 hour, then increase the temperature to 430 degrees at 2 degrees / min and keep it for 1 hour, then increase the temperature to 620 degrees at 2 degrees / min and keep it for 30 minutes, then increase the temperature to 880 degrees Celsius at 3 degrees / min and keep it for 1 hour before taking it out.

[0149] Sintering: The sintering furnace was pre-evacuated to 0.1 Pa, and then hydrogen was introduced at a gas flow rate of 0.12 cubic meters per hour; the sintering temperature was 1050 degrees Celsius and kept warm for 2 hours.

[0150] Heat treatment: The sintered parts are heat treated, with the solution temperature at 980 degrees Celsius for 2 hours and the aging temperature at 500 degrees Celsius for 2 hours.

[0151] In this scenario, a two-layer structure of a first material layer 10 (copper alloy) and a second material layer 20 (copper alloy, diamond particles, molybdenum sulfide particles) is formed, wherein the first material layer 10 ensures the strength and elongation of the layered composite material, with a yield strength of 830 MPa, an elongation of 10%, and a Vickers hardness of 310 HV, ensuring that the material will not break when falling while greatly improving the wear resistance, and the second material layer 20 ensures thermal conductivity, wherein the thermal conductivity coefficient is >400 W / mk.

[0152] Compared with the above scenario one, the composition of the copper alloy in the first material layer 10 and the second material layer 20 in the layered composite material in this scenario is the same, thereby avoiding the situation where the two different materials cause a slight difference in shrinkage rate between the first material layer 10 and the second material layer 20 in the layered composite material.

[0153] Scene 5

[0154] In this scenario, the layered composite material can be a three-layer structure, wherein the first metal material used in the first material layer 10 can be a copper alloy, and the average particle size of the copper alloy is less than 30um, wherein the weight percentage of Mn in the first metal material is 22%, the weight percentage of Ni is 16%, the weight percentage of aluminum is 3%, the weight percentage of Si is 1.3%, and the rest is copper and impurities with a weight percentage of less than 0.02% of a single element.

[0155] The first composite material used in the second material layer 20 can be a layered composite material composed of pure copper, diamond particles and molybdenum sulfide particles, wherein the average particle size of the diamond particles is less than 5um, and the average particle size of the molybdenum sulfide particles is less than 10um. After the pure copper, diamond particles and molybdenum sulfide particles are evenly mixed, the volume of the diamond particles accounts for 10%, and the volume of the molybdenum sulfide particles accounts for 10%.

[0156] In this scenario, a powder pressing process is used to connect the first material layer 10 and the second material layer 20 to form a layered composite material. First, the first metal material is placed in a pressing mold for pressing, and then the first composite material is placed in a pressing mold for pressing.

[0157] Furthermore, the laminated composite material after compression molding is sequentially sintered and heat-treated to form a laminated composite material in which the first metal material is the first material layer 10 and the first composite material is the second material layer 20. The sintering and heat-treatment processes are described below:

[0158] Sintering: The sintering furnace was pre-evacuated to 0.1 Pa, and then hydrogen was introduced at a gas flow rate of 0.12 cubic meters per hour; the sintering temperature was 1050 degrees Celsius and kept warm for 2 hours.

[0159] Heat treatment: The sintered parts are heat treated, with the solution temperature at 980 degrees Celsius for 2 hours and the aging temperature at 500 degrees Celsius for 2 hours.

[0160] After the laminated composite material after compression molding is sintered and heat-treated in sequence, a third material layer 30 is provided on the side of the second material layer 20 in the laminated composite material away from the first material layer 10. The third material used in the third material layer 300 may be diamond. Specifically, the third material layer 30 may be formed on the side of the second material layer 20 away from the first material layer 10 by a chemical vapor deposition process, that is, the side of the second material layer 20 away from the first material layer 10 may be coated to form a diamond film layer. For example, the laminated composite material after heat treatment may be placed in a chemical vapor deposition (CVD) furnace for CVD coating to form a 6-micron thick diamond film layer.

[0161] In this scenario, by forming a three-layer structure of a first material layer 10 (high-strength copper alloy), a second material layer 20 (pure copper, diamond particles, molybdenum sulfide particles) and a third material layer 30 (diamond), the layered composite material in this scenario can have properties such as high strength, high thermal conductivity and high wear resistance.

[0162] Compared with the above scenario 2, the layered composite material in this scenario is produced by a powder pressing process.

[0163] Scene 6

[0164] In this scenario, the layered composite material can be a three-layer structure, and the first metal material used in the first material layer 10 can be a copper alloy, wherein the first composite material used in the second material layer 20 can be a layered composite material composed of pure copper, diamond particles and molybdenum sulfide particles, wherein the average particle size of the diamond particles is less than 5um, and the average particle size of the molybdenum sulfide particles is less than 10um. After the pure copper, diamond particles and molybdenum sulfide particles are uniformly mixed, the volume proportion of the diamond particles is 10%, and the volume proportion of the molybdenum sulfide particles is 5%.

[0165] In this scenario, the first material layer 10 and the second material layer 20 are connected to form a layered composite material by using an insert die-casting process. First, the first composite material is placed in a pressing mold for pressing.

[0166] Furthermore, the second material layer 20 after pressing is sequentially sintered and heat treated. The sintering and heat treatment processes are described below respectively:

[0167] Sintering: The sintering furnace was pre-evacuated to 0.1 Pa, and then hydrogen was introduced at a gas flow rate of 0.12 cubic meters per hour; the sintering temperature was 1050 degrees Celsius and kept warm for 2 hours.

[0168] Heat treatment: The sintered parts are heat treated, with the solution temperature at 980 degrees Celsius for 2 hours and the aging temperature at 500 degrees Celsius for 2 hours.

[0169] After the second material layer 20 after compression molding is sintered and heat treated in sequence, the second material layer 20 is placed in a die-casting mold for insert die-casting, wherein the die-casting material is the first metal material. In this way, the first material layer 10 and the second material layer 20 can be connected to form a layered composite material by using the insert die-casting molding process.

[0170] Finally, a third material layer 30 is provided on the side of the second material layer 20 in the layered composite material away from the first material layer 10. The third material used in the third material layer 300 may be diamond. Specifically, the third material layer 30 may be formed on the side of the second material layer 20 away from the first material layer 10 by a chemical vapor deposition process, that is, a diamond film layer may be formed by coating the side of the second material layer 20 away from the first material layer 10. For example, the heat-treated layered composite material may be placed in a chemical vapor deposition (CVD) furnace for CVD coating to form a 6-micron thick diamond film layer.

[0171] In this scenario, by forming a three-layer composite structure of a first material layer 10 (high-strength copper alloy), a second material layer 20 (pure copper, diamond particles, molybdenum sulfide particles) and a third material layer 30 (diamond), the layered composite material in this scenario can have properties such as high strength, high thermal conductivity and high wear resistance.

[0172] Compared with the above-mentioned scenarios 2 and 5, the layered composite material in this scenario is manufactured by an insert die-casting process.

[0173] It is easy to understand that the above scenarios are just a few examples of the structure, material composition and manufacturing method of the layered composite material in the embodiments of the present application. The layered composite material and the manufacturing method of the layered composite material provided in the embodiments of the present application are not limited to the above examples.

[0174] like Figure 8As shown, an embodiment of the present application further provides a rotating shaft 1, which may include a fixed part 101 and a rotating part 102 rotatably connected to the fixed part 101, wherein either the rotating part 102 or the fixed part 101 may be made of the layered composite material in the above-mentioned embodiment one, or both the rotating part 102 and the fixed part 101 may be made of the layered composite material in the above-mentioned embodiment one.

[0175] By adopting the above-mentioned layered composite material, the thermal conductivity of the rotating shaft 1 is improved compared with the rotating shaft in the prior art, and it can not only bear the force and rotate, but also have the effect of heat dissipation and heat conduction.

[0176] It should be noted that the shaft 1 provided in the embodiment of the present application may include but is not limited to a personal computer (PC) shaft, a personal computer (PC) thermal shaft, a folder shaft, a folder thermal shaft, a tablet computer shaft, a tablet computer thermal shaft and other components.

[0177] The embodiment of the present application further provides an electronic device 100, which may at least include the rotating shaft 1 in the above-mentioned embodiment 2, so that the electronic device 100 forms a foldable electronic device.

[0178] Reference Fig. 9 As shown, the electronic device 100 may include a rotating shaft 1 and a first structure member 2 and a second structure member 3 that are rotatably connected to the rotating shaft 1, wherein the first structure member 2 and the second structure member 3 are rotatably connected to the fixing member 101 through a rotating member 102. In this way, the first structure member 2 and the second structure member 3 can rotate around the rotating shaft 1, so that the ends of the first structure member 2 and the second structure member 3 that are away from the rotating shaft 1 can be relatively close to or relatively far away from each other, so that the electronic device 100 can be in a folded state (see Fig. 9 ) or expand (see Fig.10 ) and other different states.

[0179] It should be noted that the number of structural members in the electronic device 100 can be two or more, and when the number of structural members is two or more, each adjacent structural member can rotate around the mutually parallel rotation axis 1, thereby forming a multi-layer folding structure, or obtaining a larger display area after unfolding. Fig.10 The following description will be made with reference to the first structural member 2 and the second structural member 3) as an example.

[0180] It is understood that the structure illustrated in the embodiment of the present application does not constitute a specific limitation on the electronic device 100. In other embodiments of the present application, the electronic device 100 may include more or fewer components than shown in the figure, or combine certain components, or separate certain components, or arrange the components differently. For example, the electronic device 100 also includes a display screen and a back cover (not shown). The illustrated components may be implemented in hardware, software, or a combination of software and hardware.

[0181] By setting the above-mentioned rotating shaft 1 in the electronic device 100, compared with the electronic device 100 in the prior art, the rotating shaft has a very low thermal conductivity and only plays the role of bearing force and rotating, but not the role of heat dissipation. The embodiment of the present application optimizes the experience effect of the electronic device 100. At the same time, it also ensures the stability of signal transmission in the electronic device 100 and ensures the normal operation of the electronic device 100.

[0182] It should be noted that the electronic device 100 provided in the embodiment of the present application may include but is not limited to a mobile phone, a tablet computer, a laptop computer, a personal computer (PC), a wearable device, a virtual reality device, and other mobile or fixed terminals having the above-mentioned hinge 1.

[0183] In the description of the embodiments of the present application, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, or it can be an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in the embodiments of the present application can be understood according to specific circumstances.

[0184] In the embodiments of the present application, the devices or elements referred to or implied must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the embodiments of the present application. In the description of the embodiments of the present application, the meaning of "multiple" is two or more, unless otherwise precisely and specifically specified.

[0185] The terms "first", "second", "third", "fourth", etc. (if any) in the specification and claims of the embodiments of the present application and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchangeable where appropriate, so that the embodiments of the embodiments of the present application described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any of their variations are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device comprising a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0186] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the embodiments of the present application, rather than to limit them. Although the embodiments of the present application have been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A layered composite material, characterized in that: include: At least two material layers arranged in a stacked manner; Wherein, the at least two material layers include adjacent first material layer and second material layer; The first material layer is made of a first metal material, the yield strength of the first metal material is greater than 200 Mpa, and the elongation of the first metal material is greater than 6%; The second material layer adopts a first composite material, and the first composite material includes a second metal material, molybdenum sulfide particles and diamond particles; The first material layer and the second material layer contain a binder; It also includes a third material layer that is attached to the second material layer, the second material layer is arranged between the first material layer and the third material layer; the third material layer is made of diamond; The Vickers hardness of the third material layer is greater than the Vickers hardness of the first metal material, and the thermal conductivity of the third material layer is greater than the thermal conductivity of the first composite material.

2. The layered composite material according to claim 1, characterized in that The diamond particles are at least partially located on a surface of the second material layer away from the first material layer.

3. The layered composite material according to claim 1 or 2, characterized in that: The third material layer is exposed on one side facing away from the second material layer.

4. The layered composite material according to claim 1 or 2, characterized in that: The first metal material and the second metal material have the same main element, and the main element is the element with the largest proportion in the first metal material and the second metal material.

5. The layered composite material according to claim 4, characterized in that The first metal material includes one of a copper alloy and pure copper, and the second metal material includes one of a copper alloy and pure copper.

6. The layered composite material according to claim 4, characterized in that The first metal material includes one of stainless steel and alloy steel, and the second metal material includes one of stainless steel and alloy steel.

7. The layered composite material according to any one of claims 1, 2, 5 and 6, characterized in that: The average particle size of the molybdenum sulfide particles is less than 15 um.

8. The layered composite material according to any one of claims 1, 2, 5 and 6, characterized in that: The average particle size of the diamond particles is less than 10 um.

9. The layered composite material according to any one of claims 1, 2, 5 and 6, characterized in that: The volume fraction of the diamond particles in the first composite material is greater than or equal to 5%.

10. The layered composite material according to claim 9, characterized in that The volume fraction of the diamond particles in the first composite material is greater than or equal to 25%.

11. The layered composite material according to any one of claims 1, 2, 5, 6 and 10, characterized in that: The layered composite material is formed between the first material layer and the second material layer by a metal injection molding process.

12. The layered composite material according to any one of claims 1, 2, 5, 6 and 10, characterized in that: The thickness of the second material layer is greater than 0.1 mm.

13. The layered composite material according to any one of claims 1, 2, 5, 6, and 10, characterized in that: The thickness of the third material layer is less than 10 um.

14. A rotating shaft, characterized in that: It comprises a fixing part and a rotating part rotatably connected to the fixing part, wherein any one of the rotating part and the fixing part or both the rotating part and the fixing part are made of the layered composite material according to any one of claims 1 to 13.

15. An electronic device, characterized in that: At least comprises the rotating shaft as described in claim 14 above.

16. A method for preparing a layered composite material, characterized in that: include: providing at least a first metal material and a first composite material; The first metal material is used as the first material layer, the yield strength of the first metal material is greater than 200Mpa, and the elongation of the first metal material is greater than 6%; the first composite material is used as the second material layer, and the first composite material includes a second metal material, molybdenum sulfide particles and diamond particles; the first material layer and the second material layer contain a binder; connecting the first material layer and the second material layer to form the layered composite material; providing diamond as the third material layer; The third material layer is arranged between the second material layer and the first material layer in the layered composite material, and the third material layer is adjacent to the second material layer; The Vickers hardness of the third material layer is greater than the Vickers hardness of the first metal material, and the thermal conductivity of the third material layer is greater than the thermal conductivity of the first composite material.

17. The method for producing a layered composite material according to claim 16, characterized in that: The step of connecting the first material layer and the second material layer to form a layered composite material specifically includes: The first material layer and the second material layer are connected to form the layered composite material by using a metal injection molding process.

Citation Information

Patent Citations

  • Layer-shaped high thermal conductive and insulating base plate and preparation method thereof

    CN104733399A

  • Heat dissipation member and method for producing heat dissipation member

    CN106688092A

  • Preparation method of diamond wire saw beads based on bimetallic powder injection molding

    CN110653370A

  • Rotating shaft for notebook computer

    CN201866083U